2022
DOI: 10.1038/s41467-022-28138-6
|View full text |Cite
|
Sign up to set email alerts
|

Formyl peptide receptor 2 determines sex-specific differences in the progression of nonalcoholic fatty liver disease and steatohepatitis

Abstract: Nonalcoholic fatty liver disease (NAFLD) is an important health concern worldwide and progresses into nonalcoholic steatohepatitis (NASH). Although prevalence and severity of NAFLD/NASH are higher in men than premenopausal women, it remains unclear how sex affects NAFLD/NASH pathophysiology. Formyl peptide receptor 2 (FPR2) modulates inflammatory responses in several organs; however, its role in the liver is unknown. Here we show that FPR2 mediates sex-specific responses to diet-induced NAFLD/NASH. NASH-like l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 52 publications
3
27
0
Order By: Relevance
“…64 Lastly, lack of choline will impair VLDL secretion and subsequent fat accumulation. 65 In this study, PCO treatment effectively curbed the increase of S1P and the reduction of choline in the liver tissues of HFD-fed mice ( P < 0.01, vs. the HFD group) (Fig. 9E and F).…”
Section: Resultssupporting
confidence: 56%
“…64 Lastly, lack of choline will impair VLDL secretion and subsequent fat accumulation. 65 In this study, PCO treatment effectively curbed the increase of S1P and the reduction of choline in the liver tissues of HFD-fed mice ( P < 0.01, vs. the HFD group) (Fig. 9E and F).…”
Section: Resultssupporting
confidence: 56%
“…and progression of NAFLD, and the severe damage seen in FPR2-depleted females supports FPR2's protective role in female mice's liver (49). In addition to sex, race, age, and other covariates may also be factors influencing the relationship between SII and CAP, and multiple factors interacting with each other may also be the reason why the relationship between SII and CAP in this study was not significant in model 2 and model 3.…”
Section: Discussionmentioning
confidence: 47%
“…Men with NAFLD have more severe hepatic steatosis than women, and postmenopausal women have greater hepatic steatosis than premenopausal women, according to several studies, suggesting that the gender difference in NAFLD is related to sex hormones ( 47 , 48 ). Furthermore, a recent experimental animal study found that Formyl Peptide Receptor 2 (FPR2) expression is higher in female mice than that in male mice, making females more resistant to the development and progression of NAFLD, and the severe damage seen in FPR2-depleted females supports FPR2’s protective role in female mice’s liver ( 49 ). In addition to sex, race, age, and other covariates may also be factors influencing the relationship between SII and CAP, and multiple factors interacting with each other may also be the reason why the relationship between SII and CAP in this study was not significant in model 2 and model 3.…”
Section: Discussionmentioning
confidence: 99%
“…This would be distinct from CCR2 inhibition, which will not affect the KCs, but rather solely alter monocyte recruitment to tissues. Alternatively, another study has suggested that the receptor is expressed by hepatocytes [ 26 ], thus perhaps hrAnxA1 treatment acts directly on these cells preventing lipotoxicity and hence the need to generate LAMs. The precise reasons for the differences in terms of expression of the receptor are unclear and hence require further investigation but this may be due to differences between mRNA and protein expression.…”
mentioning
confidence: 99%
“…The precise reasons for the differences in terms of expression of the receptor are unclear and hence require further investigation but this may be due to differences between mRNA and protein expression. Moreover, as the expression has been shown to be positively correlated with levels of Estradiol [ 26 ], the differences in expression could be due to sex in the RNA-seq study. Another hypothesis regarding the mechanism of action of hrAnxA1 would be that hrAnxA1 treatment specifically interferes with monocyte to LAM differentiation, resulting in a reduced population of LAMs ( Figure 1 ).…”
mentioning
confidence: 99%